A comprehensive review of vehicle detection using computer vision - Aymen Fadhil Abbas; Usman Ullah Sheikh; Fahad Taha AL-Dhief; Mohd Norzali Haji Mohd (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
A crucial step in designing intelligent transport systems (ITS) is vehicle detection. The challenges of vehicle detection in urban roads arise because of camera position, background variations, occlusion, multiple foreground objects as well as vehicle pose. The current study provides a synopsis of state-of-the-art vehicle detection techniques, which are categorized according to motion and appearance-based techniques starting with frame differencing and background subtraction until feature extraction, a more complicated model in comparison. The advantages and disadvantages among the techniques are also highlighted with a conclusion as to the most accurate one for vehicle detection.